The Macro Financing of Natural Hazards in Developing Countries - Mahul, Olivier; Gurenko, Eugene (World Bank, Washington, DC, 2012)
The authors propose a financial model to address the design of efficient risk financing strategies against natural disasters at the country level. It is simple enough to shed analytical light on some of the key issues but flexible and realistic enough to provide some quantitative guidance on the ex ante financing of catastrophic losses. The risk financing problem is decomposed into two steps. First, the resource gap, defined as the difference between losses and available ex-post resources (such as post-disaster aid), is identified. It determines the losses to be financed by ex ante financial instruments (reserves, catastrophe insurance, and contingent debt). Second, the cost-minimizing financial arrangements are derived from the marginal costs of the financial instruments. The model is solved through a series of graphical analyses that make this complex financial problem easier to apprehend. This model captures and explains the main impacts of financial parameters (such as insurance premium, cost of capital) on efficient risk financing structures.